2020
DOI: 10.1002/adma.202000338
|View full text |Cite
|
Sign up to set email alerts
|

Binding Zinc Ions by Carboxyl Groups from Adjacent Molecules toward Long‐Life Aqueous Zinc–Organic Batteries

Abstract: storage. [2][3][4][5][6][7] Among them, aqueous zinc batteries have aroused extensive interest and attention, which benefits from many advantages of zinc anode, including high theoretical capacity (820 mAh g −1 ), appropriate redox potential (−0.762 V vs the standard hydrogen electrode (SHE)), and intrinsic safety in aqueous system. [8][9][10][11][12][13][14][15][16][17][18][19][20] Inspired by conventional Li + storage reaction, intercalation reaction of transition metal oxides are employed to storage Zn 2+ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
232
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(234 citation statements)
references
References 51 publications
2
232
0
Order By: Relevance
“…[32,41] However,s ulfur heterocyclic quinone dibenzo[b,i ]thianthrene-5,7,12,14-tetraone (DTT) could reversibly store both Zn 2+ and H + . [42] Different from carbonyl compounds,animine compound, diquinoxalino [2,3a:2 ',3'-c] phenazine (HATN), can achieve H + uptake/ removal by coordination/incoordination reaction in mild electrolyte. [36] Different from n-type counterparts,p -type organic electrode materials will first undergo oxidation process.D uring the oxidation, they will loss electrons and change into cations.…”
Section: Energy Storage Mechanismmentioning
confidence: 99%
“…[32,41] However,s ulfur heterocyclic quinone dibenzo[b,i ]thianthrene-5,7,12,14-tetraone (DTT) could reversibly store both Zn 2+ and H + . [42] Different from carbonyl compounds,animine compound, diquinoxalino [2,3a:2 ',3'-c] phenazine (HATN), can achieve H + uptake/ removal by coordination/incoordination reaction in mild electrolyte. [36] Different from n-type counterparts,p -type organic electrode materials will first undergo oxidation process.D uring the oxidation, they will loss electrons and change into cations.…”
Section: Energy Storage Mechanismmentioning
confidence: 99%
“…Furthermore, some findings have suggested that H + existing in the mild aqueous electrolyte can react with carbonyl groups to form phenol before or in parallel with the storage of Zn 2+ . [39,40] Moreover, part of phenol group can release electrons when reversibly oxidized into the corresponding quinone group. [41,42] Thus, two cathodic peaks located at 0.47 and 0.85 V in the CV curve correspond to simultaneous Zn 2+ binding and the concerted reduction of o-quinone to phenol, respectively.…”
Section: (5 Of 9)mentioning
confidence: 99%
“…The HATN//Zn battery demonstrated fast kinetics and a long‐term cycling life as a consequence of the reversible structural evolution of HATN, with a capacity retention of 93.3 % after 5 000 cycles at 5 A g −1 . Recently, our group proposed a Zn–organic battery that uses dibenzo[ b , i ]thianthrene‐5,7,12,14‐tetraone (DTT) and Zn foil as cathode and anode, respectively, with a mild electrolyte containing Zn 2+ . Using electrochemical measurements, ex situ analyses, and DFT calculation, we demonstrated that the DTT electrode can simultaneously store both H + and Zn 2+ to form DTT 2 (H + ) 4 (Zn 2+ ).…”
Section: Insoluble Organic Electrodes In Aqueous Electrolytes For Enementioning
confidence: 99%
“…Furthermore, Compared to monovalent ions, reduced storage of divalent ions in host materials is needed to exert an equal capacity, which leads to a lower volume change of organic materials. The coordination reaction can also be used to reversibly store the hydronium (H 3 O + ), indicating the possibility of developing the organic hydronium batteries . Furthermore, the soluble organic molecules can be used as active materials for flow batteries .…”
Section: Introductionmentioning
confidence: 99%